(untitled) (REMUNOM, 2025)
Introduction: The increasing dissemination of drugs and treatments through social media has significantly contributed to the rise of self-medication, due to easy and fast access to information, often without scientific basis. The present study sought to understand how social media influences the irrational use of medicines. Method: The research was developed through an integrative literature review, with a qualitative approach and descriptive nature. Scientific productions were analyzed based on a systematic search in the Scopus (Elsevier) and PubMed databases, with the objective of gathering different evidence and perspectives on the topic. The analysis focused on three main axes: (i) the influence of social media on the promotion of self-medication, (ii) the consequences of improper use of medicines, and (iii) the importance of health education in developing effective strategies for public awareness. Results: It was identified that social media promotes self-medication, highlighting the normalization of using medicines without a medical prescription, the difficulty users have in distinguishing personal accounts from clinical recommendations, and the vulnerability of less-informed groups to unregulated online content. Emotional factors, such as anxiety (especially during health crises), also influence the decision to resort to self-medication. However, well-planned educational interventions can transform these perceptions and increase the adoption of preventive behaviors. Conclusion: Therefore, the development of effective educational strategies is essential to help individuals make informed decisions about their care. The fight against self-medication influenced by social media requires a multidisciplinary and integrated approach, based on health education, digital responsibility, and collective commitment.